(untitled) (Research, Society and Development, 2025)
Bees play an essential role in the pollination of crops of commercial interest and, consequently, in the maintenance of ecosystems, in addition to being vital for beekeeping activity. For the success of the activity, the annual replacement of queen bees is recommended to maintain the population development of the colony and, thus, productivity. Thus, beekeepers who showed interest in participating in the research were selected. The objective of the present investigation is to study the production of queen trees by small beekeepers in a non-commercial way in comparison to the productivity percentages reported by the scientific community, to verify the feasibility of this strategy. For this, beekeepers who showed interest in participating in the research were selected. Then, based on individual productivity, hives were selected to be used as larval donors, which were transferred to artificial queens (manually made with beeswax) containing a drop of royal jelly from a single batch. Then, these artificial queens were transferred to hives containing orphaned colonies at different periods to verify the production of queens. Then, when the queens were operculated, the number of accepted queens and the birth of princesses were determined. The data were analyzed by descriptive analysis. The research revealed that the queen production method can be a viable strategy for small beekeepers, allowing genetic improvement and diversification of production. However, more research is needed to optimize the process and increase efficiency.